Exploring the Correlation between Motivation and Self-Regulation in Science Learning among Junior High School Students: A Case Study - Sholahudin, Nabila Putri; Shofa Nabilah; Nimas Ayu Lestari; Adi Rahmat; Nanang Winarno; Yanti Hamdiyati (Universitas Negeri Semarang, 2024)
A student's motivation influences students' self-regulatory abilities, and significantly impacts their attitude towards scientific concepts, contributing to a more enriched and successful learning experience. This research explores the correlation between motivation and self-regulation in science learning among junior high school students. The research methodology employed in this study adopts a quantitative approach with a survey research design. This research found that the average learning goal orientation is 4.12, task value is 3.97, and self-efficacy is 3.75. The total average for the dimensions of motivation and self-regulation is 3.95 and 3.89 respectively. These scores indicate that the motivation and self-regulation in science learning among junior high school students are categorized at a high level. Furthermore, there is a significant correlation between motivation dimensions (learning goal orientation, task value, and self-efficacy) and self-regulation in science learning. Based on the students’ answers to open-ended questions, they are motivated to learn science because learning science is interesting and fun. Meanwhile, students who feel unmotivated to learn science find it challenging, especially when dealing with formulas and calculations. However, despite the lessons' difficulty, students still try to study because most of them desire to achieve good grades in science lessons.